A methodological approach for the simultaneous quantification of glycerol and fatty acids from cork suberin in a single GC run - V Marques, A (2019)
Introduction: Suberin, as part of plant protective barriers, is one of the most important natural polymers after cellulose and lignin. For a full elucidation of suberin structure the quantification of glycerol, fatty α,ω‐diacids and ω‐hydroxyacids, the major building blocks of suberin, is of primary importance. Glycerol is often lost in the most used analytical procedures or rarely determined by deficient or too laborious techniques. Objectives: Propose a simple, accessible and reliable methanolysis work‐up procedure for an accurate and simultaneous quantification of glycerol and suberin fatty monomers in the same GC run. Material and methods: Cork from Quercus suber L. was depolymerised by methanolysis. Glycerol was derivatised to an organic soluble form before the suberin monomers recovery in water/organic solvent partition. Gas chromatography flame ionisation detector (GC‐FID) response factors were determined for glycerol, ferulic acid and one for each fatty monomer substructure. Additionally, 1,2,4‐butanetriol and methyl nonadecanoate were used as internal standards. Results: The proposed experimental approach allowed the glycerol and all the fatty suberin monomers in the same GC run to be quantified accurately. Glycerol represented 30.6 area%, 14.2 mass% and 38.4 molar% of suberin and the COOH/OH groups ratio was 0.6:1 in the proposed experimental approach in contrast with 0.10 area% and COOH/OH ratio of 3:1 in the most used protocol. Furthermore, ω‐hydroxyacids/α,ω‐diacids mass ratio was 1:1 as opposed to an area ratio of 1.5:1. Conclusion: The proposed work‐up procedure revealed to be a reliable analytical tool for the complete analysis of suberin allowing the future knowledge to grow towards a better understanding of suberin structure throughout its range and variability.